(untitled) (Bioagro, 2020)
To evaluate the effect of nitrogen fertilization on corn yield and grain quality, a trial was conducted at a rural settlement in Arenales, Aragua State, Venezuela. An experimental design in randomized complete blocks with a split plot arrangement of treatments with three repetitions was used. Main plots were six corn hybrids: two semi-dents, two semi-flints and two flints, and subplots were fertilization treatments. Each experimental unit had plots of 3.6 x 4.0 m with four rows 4 m length spaced 0.9 m apart and 0.20 between plants. The N fertilizer was applied in two fractions: at planting time and 30 days after. Three rates were used (100, 150 y 200 kg∙ha-1) plus a control without N fertilizer. Additionally, all plants received 35 kg∙ha-1 P2O5 and 60 kg∙ha-1 K2O at planting time. Number of days elapsed until flowering and plant maturity, ear length and diameter, number of rows of grains per ear, weight of 1000 grains and yield were determined; it was carried out a proximal chemical analysis and amino acids in harvested grain as well. All hybrids showed higher yields at 150 kg∙ha-1 N. Results indicated a positive and significant effect of nitrogen fertilization over productivity parameters. The hybrid DK-7088 had the longest time from sowing to flowering and to ripening. The higher protein percentages were obtained in fertilized treatments, although as an average, the hybrids with the highest yields showed the lowest levels of protein. Nitrogen fertilization influenced positively lysine content.